Certification Corner A Monthly Quiz. Issue 10 (1st October 2016) - Unknown
Abstract : Certification Corner lets Opflow readers sharpen their skills with a quick quiz of terminology, regulations, practices, and formulas pertinent to water/wastewater distribution system and treatment plant operations.